KONTEKSTUALISASI HADIS TENTANG PENGURUSAN JENAZAH: STUDI ATAS SYARAH HADIS KITAB FATH AL-BAARI - Dhulkifli, Muhammad Luthfi (Universitas Islam Negeri Raden Fatah Palembang, 2019)
Syarah hadis books which have existed are in the track of normative interpretation and t it less supporting our current issues. It is also happened with Fath al-Baari as one of famous and comprehensive syarah hadith book. Current issues such rejection of funeralal pray in Jakarta during governor election 2017 is the clear example. This phenomenon is related with hadith and hardly ever response by every single syarah hadis book so far. Toward this condition, it is important to see the rejection phenomenon of funeral prayer and the hadith in the contextualization method. This article will try to describe several hadith in case of funeral prayer with some interpretation based on Fath al-Baari and another syarah hadith book. To conclude, there is a contextualizationn method to give better actualization of understanding toward previous syarah hadith and avoid normative interpretation.